Pengaruh Media Pembelajaran Video Animasi dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA - Karlenata, Hiis; Yumarni, Asmara; Astuti, Dina Putri Juni (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines the effect of animated video media on the science learning outcomes of fifth grade students of SDN 77 Seluma, who have difficulty reading due to less participatory learning methods. Using a quasi-experimental design, this study compared class VB (experimental) using animated videos with class VA (control) with conventional learning. The sampling technique was propesive sampling with data collection instruments through observation, interviews, documentation, and multiple-choice tests. Data analysis used normality tests, homogeneity, t-tests, and simple linear regression. The results showed significant differences between the two groups (mean post-test value of the experiment = 96 vs control = 74). The t-test proved the effect of animated media (sig. 0.003 <0.05) so that Ha was accepted. These findings prove that animated videos are effective in improving science learning outcomes through a more interactive and enjoyable learning approach.